Management Of Immune Formation for Covid-19 Prevention Through Vaccination - I Irnawati; Benny Arief Sulistyanto; Nuniek Nizmah Fajriyah (Urecol Journal. Part C: Health Sciences, 2021)
The Covid-19 disease is still very high in transmission. The total number of confirmed Covid-19 patients on October 9, 2021 is 5615 people (Pekalongan City), 7927 people (Pekalongan Regency) and 320 people (Pekalongan City), 562 people (Pekalongan Regency) died from Covid-19. The existence of a vaccine is clearly the best hope to reduce the transmission rate of the Covid-19 virus which is getting out of control. Vaccines and health education about the benefits of the Covid-19 vaccine and Post-Immunization Adverse Events (AEFI) aims to: (1) increase knowledge about the benefits of the Covid vaccine -19 to prevent the transmission of Covid-19; (2) increase public awareness to carry out the Covid-19 vaccine and not panic if AEFIs appear. The target of this community service is consisting of students and alumni of Pekajangan Muhammadiyah University, people from Pekalongan Regency, Pekalongan City, Batang Regency, Pemalang Regency and several other communities in Central Java area. The activities include registration and verification of data, screening history and simple physical examinations, as well as conducting education on Covid-19 vaccination, implementation of vaccines, submission of vaccine certificates and health education regarding AEFI. The results of this community service activity are that 1600 people have been vaccinated, know about the benefits of vaccines and AEFI. It is hoped that people who have been vaccinated will continue to apply the 5M health protocol (wearing masks, washing hands with soap, maintaining distance, limiting mobility and staying away from crowds).